The Aquanaut - Santat, Dan (Graphix, 2022)
Five years ago, Sophia's father was lost at sea during an research mission, and she now spends her days at Aqualand, the marine theme park her dad and uncle created. But everything changes when an "aquanaut" breaks into the park's research lab, and she discovers it's piloted by four intrepid sea creatures. When the creatures learn of the increasing commercialization of Aqualand, they set out to free their fellow marine life with the help of Sophia.